A new genus and species of Agraeciini (Orthoptera: Tettigoniidae: Conocephalinae) from Amazon Rainforest - Tavares, Gustavo Costa (Zootaxa, 2020)
This paper describes a new genus and species of Agraeciini from the Brazilian Amazon Rainforest, Wuyjugu pizai gen. et sp. nov., the 23rd species of Agraeciini recorded in Brazil. The female bears a very long and straight ovipositor, while the male has a completely membranous phallic complex, traits not seen in any of the Agraeciini genera of South-America.